NNW-GridStar: Interactive structured mesh generation software for aircrafts. (July 2020) - Lu, Fengshun; Qi, Long; Jiang, Xiong; Liu, Gang; Liu, Yang; Chen, Bo; Pang, Yufei; Hu, Xingzhi
Highlights: Developing a piece of interactive multiblock structured mesh generation software. Supporting automatic boundary-layer mesh generation. Proposing techniques to accelerate volume mesh generation, such as rapid block assembly, multiblock stretching, and O-type block stretching. Improving software usability through the undo/redo functionality. Abstract: The structured meshes are widely utilized in the aircraft industry because of their efficiency in achieving accurate solutions, especially for viscous flows of complex configurations. However, they are usually generated by engineers through enormous and tedious interaction with the graphical user interface of mesh generation software. To address this issue, we implement one piece of interactive structured mesh generation software called NNW-GridStar. First, we present its design details, including the software architecture and data structure. Second, we demonstrate its implementation and emphasize on the accelerated techniques proposed in our software, which consist of automatic boundary-layer mesh generation, rapid block assembly, multiblock stretching, and O-type block stretching. Finally, we perform a deep comparison between the developed NNW-GridStar and another two pieces of well known commercial software, and then demonstrate the application of NNW-GridStar in the productional CFD simulations. Experimental results show that NNW-GridStar has an outstanding generation speed and can produce meshes with high quality.